The organization of the alpha-tubulin gene family in the Drosophila montium subgroup of the melanogaster species group. - Drosopoulou, E.; Scouras, Z.G. (Genome, 1998)
The alpha 1-, alpha 2-, alpha 3-, and alpha 4-tubulin genes have been mapped by in situ hybridization to the polytene chromosomes of five species representative of the Drosophila montium subgroup geographical distribution. A lambda phage clone containing alpha 1-tubulin specific sequences was isolated from a genomic DNA library of Drosophila auraria and its restriction endonuclease pattern is presented. Both well-characterized heterologous and homologous probes were used to assess orthogonality of gene members between species groups. The in situ hybridization pattern observed in all species studied is consistent with that of Drosophila melanogaster, since alpha 1-, alpha 2-, and alpha 3-tubulin genes are located on the same polytene arm, and the alpha 4-tubulin gene is found on a different arm. Cross-hybridization was observed among alpha 1-, alpha 2-, and alpha 3-tubulin specific sequences in all species studied, using either heterologous or homologous probes. However, unlike D. melanogaster, in all montium species studied, both alpha 1- and alpha 3-tubulin specific probes hybridize to the same polytene band, indicating a clustered organization of the above genes. The chromosomal organization of this gene family would suggest that taxa within the montium subgroup are closer to their common ancestors than are the taxa in the melanogaster species group. A mode of evolution for this gene family in Drosophila is proposed.